(untitled) (Asian Journal of Medical and Biological Research, 2016)
The trial was conducted at Bangladesh Livestock Research Institute (BLRI) regional station, Baghabari, Shajadpur, Sirajgonj to determine the biomass yield, morphological characteristics and nutritive value with the effect of different sources of organic manure such as biogas slurry, broiler litter and layer litter for fodder production. Significant (P<0.05) difference was observed in biomass yield among different treatment group. Biomass yield (t/ha) was in order of biogas slurry (26.80)> fertilizer (26.56)> broiler litter (22.34)>layer litter (22.20). This study also showed that DM yield and survival percentage were also significantly (P?0.05) differed among the treatments. The DM% in all groups was mostly similar but DM yield (t/ha) was the highest (3.94) in biogas slurry and the lowest (3.13) in layer litter. The cost (Tk/ha) was significant (P<0.01) difference among the treatment group. The highest cost (15856Tk/ha) was observed in fertilizer group and the lowest (5705 Tk/ha) was biogas slurry group. There was no significant (p>0.01) effect of different organic manures on nutritive value of BLRI Napier-4. It may be suggested that biogas slurry may be used as sources of fertilizer for fodder cultivation. Asian J. Med. Biol. Res. December 2015, 1(3): 690-692